AN INVESTIGATION ON COMPLAINTS OF NOISE FROM MRT CONSTRUCTION SITES - NG YI NING EVANGELINE (2017)
This dissertation examines the key areas of concern affecting the residents, the methods applied by the contractors to mitigate noise, and how effective are these methods. The research design is a case study in Zion Road with an ongoing construction work at Havelock Station under LTA’s Thomson-East Coast Line. It is an interpretive study on the affected parties are to understand the different points of view. Here “noise” is not an objective category, that is, it may be contested and subject to different interpretations.